International Student Recruitment Strategies in Finland and China: An Analysis of Website Content - Jokila, Suvi (Nordic Journal of Comparative and International Education (NJCIE), 2019)
The recruitment of international students has become a global phenomenon. Prospective candidates planning to study abroad rely on different sources of information in their decision-making processes, provided by different national, institutional and private actors. Thus, more analysis of the mediators facilitating this encounter of recruiters and students is needed. This study analyses how study choices in Finland and China are constructed by analysing the embeddedness of national recruitment strategies in websites, the construction of study choices as capitals and the trust-building devices (dispositifs) employed in the websites. Data consist of textual material from four websites representing educational offerings in Finland and China, targeted for international students searching for information in their study-abroad decision-making. This study puts forward three arguments. First, the analysed websites reflect the national strategies on the recruitment of international students; however, the approaches the websites use vary greatly. Second, websites construct expectations that build on a holistic study-abroad experience. Third, non-governmental websites employ commercially oriented dispositifs to distinguish or affirm choices.